Diphenyl Diselenide – catalyzed Reductive Coupling of Nitroarenes to Aromatic Azo and Azoxy Compounds with Sodium Borohydride in Alkaline Ethanol - Belattar, Nadjah; Benayache, Samir; Benayache, Fadila (Current Organic Synthesis, 2018)
Aim and Objective: A simple catalytic method has been developed to achieve the reduction of nitroarenes with NaBH4 using diphenyl diselenide catalyst in order to obtain the azoxyarene, azoarene products under mild conditions. Materials and Methods: The reduction of different substituted nitroarenes was realized in alkaline ethanolic solution using mild sodium borohydride in the presence of diphenyl diselenide as an electron-transfer catalyst. The reactions were performed sometimes at room temperature and sometimes at refluxing conditions. Results: Diphenyl diselenide which is reduced to sodium phenylselenolate, presenting an electron transfer agent successfully permitted to reduce several nitroarenes, bearing different substituent groups whose electronic effects promote the formation of the azoxy or azo compounds. Conclusion: Treatment of nitroarenes with sodium borohydride in alkaline ethanol in the presence of catalytic amounts of diphenyl diselenide at room temperature leads to obtain the corresponding azoxy compounds in good yields by reaction with sodium phenylselenolate generated in situ. At higher temperature, further reduction to azo compounds occurs. Therefore, the results have indicated that the electronic effects of substituent groups rigorously take part in determination of their reduction efficiencies.
Keywords: azoarene